From Aliens to Citizens: The Political Incorporation of Immigrants - Pieter Bevelander; Mikael Spång (Institute for the Study of Labor (IZA), 2014)
This is a draft chapter for the Handbook on Economics of International Migration (Eds. B. R. Chiswick and P. W. Miller) and deals with the political incorporation of immigrants in host societies. Political incorporation is discussed with regard to the regulation of legal status, rights, opportunities, and acquisition of citizenship. We give examples of the legal regulation and policies from several countries in the world, showing thereby the diversity of approaches to political incorporation but also similarities to the regulation of access to residence, rights, and citizenship. We highlight changes in this regard since the Second World War and discuss more recent trends. Moreover, we discuss different factors explaining the variation in incorporation policies. Also, this chapter traces different dimensions of political participation of immigrants, and, finally, we address the expected effects on wider integration of citizenship acquisition.
Keywords: D72; J15; J61; 330; political participation; minorities; immigration; political incorporation; naturalization; citizenship; non-citizens; rights